(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2025)
In light of the increasing competition between major organizations to attract talents, and the growth of skills, the financial element is no longer the basic or only element in attracting talents or retaining talents within organizations. Attention has begun to be paid to the concept of (EVP) (Employee Value Proposition), which is the value provided to the employee in an attempt to classify the organization itself as an organization that attracts distinguished talents in the labor market. The current research aims to know the impact of the employee value provided EVP represented by its five dimensions (belonging, work content, compensation, career path, entitlements) on job creativity in its three dimensions (originality and intellectual fluency, implementing change, solving problems). To achieve the study objective, Asiacell Communications Company in Baghdad was chosen as a study community, and a sample of its employees was chosen from it, amounting to (200) individuals. A questionnaire form was prepared for all data, and it was sent to the respondents electronically via the (Google Forms) program. This data was processed descriptively via SPSS v.28 and the AMOS V.26 structural modeling equation ,This research reached a number of conclusions, the most important of which is that EVP is an important and decisive matter for the purpose of achieving job creativity, as well as enhancing Asiacell’s position in the labor market. A set of recommendations were put forward, the most important of which is enhancing the employee value through the development courses provided to them, and retaining talented employees. Keywords: Employee Value Proposition (EVP), Belonging, Job Content, Compensation, Career Path, Benefits, Functional Creativity.